Immunological and clinical follow up of hepatitis C virus associated cryoglobulinaemic vasculitis. Issue 4 (1st April 2001) - Lamprecht, P; Moosig, F; Gause, A; Herlyn, K; Csernok, E; Hansen, H; Gross, W L
Abstract : OBJECTIVE: To study immunological markers and compare these markers with standard measures for the clinical and immunological follow up of vasculitis activity in hepatitis C virus (HCV) associated cryoglobulinaemic vasculitis (CV). METHODS: Serial serum samples from eight patients with newly diagnosed HCV associated CV were followed during interferon α treatment induced remission of the CV. Vasculitis activity and disease extent were evaluated with the Birmingham vasculitis activity score (BVAS) and disease extent index (DEI). Cryoglobulinaemia, complement levels (C3c, C4, and CH50), rheumatoid factor (RF), autoantibodies such as antinuclear antibodies, soluble interleukin 2 receptor (sIL2r), soluble intercellular adhesion molecule-1 (sICAM-1), and soluble CD30 (sCD30) were determined. RESULTS: All patients achieved either complete or partial remission of their CV during interferon α treatment. There was a significant reduction in vasculitis activity and disease extent (BVAS, DEI), cryoglobulinaemia, RF, sIL2r, sICAM-1, and sCD30. Complement C3c levels increased significantly during this period. Erythrocyte sedimentation rate and levels of complement C4 and CH50 did not change significantly. Both clinical measures (BVAS and DEI) correlated significantly only with C3c and sCD30. CONCLUSIONS: Although this study was of only a small group of patients, it shows that BVAS and DEI as clinical measures and C3c and sCD30 as immunological markers may be useful in the follow up of disease activity of HCV associated CV. The data indicate that activity of the humoral (cryoglobulinaemia, RF, autoantibodies) and cellular (sIL2r, sICAM-1, sCD30) immune response and endothelial damage (sICAM-1) are found in HCV associated CV.